Analisis OEE (Overall Equipment Effectiveness) dan Six Big Losses dalam Menilai Efektivitas Mesin CNC Pada Proses Produksi PT DEF - Tantan Tandiansyah; Melinda Cryselia Maysandi Limbong; Sulaksono Mahesa Putra; Tiaradia Ihsan (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
This research is motivated by initial findings indicating that the Computer Numerical Control (CNC) machines at PT DEF exhibit various operational inefficiencies, including high downtime, unstable production speed, and an increased number of defective products. These conditions suggest that machine effectiveness is not yet optimal and may negatively affect productivity while increasing operational costs. Therefore, this study aims to evaluate the level of Overall Equipment Effectiveness (OEE) and identify the categories of the Six Big Losses that contribute most significantly to the decline in machine performance. The study was conducted through the calculation of OEE components (availability, performance, and quality) and an analysis of the Six Big Losses based on direct observations, interviews with operators, and production data from January to March 2025. The results indicate that the average OEE value of  82,98% remains below the international standard of 85%. The largest losses originate from Breakdown Losses at 38% and Idling & Minor Stoppages at 20%, followed by Reduced Speed and Defect in Process, each contributing 12%. These findings demonstrate that machine reliability and production process stability are the dominant factors requiring improvement. Accordingly, strengthening preventive maintenance and optimizing operational parameters are recommended to enhance production effectiveness. Keywords: CNC Machine, Overall Equipment Effectiveness, Preventive Maintenance, Six Big Losses